Penerimaan Sistem Inlislite di Dinas Perpustakaan dan Arsip Deli Serdang - Mehlan Ainul Firdaus (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This study is about librarians' acceptance of the Inlislite system at the Library and Archives Service of Deli Serdang Regency. The purpose of this study is to determine the impact of the Technology Acceptance Model (TAM) on the Inlislite system at the Library and Archives Service of Deli Serdang Regency. Users have different levels of technical knowledge and may face different levels of difficulty in operating the system. The research method used is descriptive research method with a quantitative approach. The respondents used for this study were 80 library visitors. A 4-point Likert scale will be used to distribute questionnaires. From the survey results and data analysis, the majority of users gave a positive response to the acceptance of the Inlislite system. This positive response shows from the level of ease of use, usefulness, behavior, intention, and real action towards the technology system. This shows that users' understanding of the benefits, ease of use, and support provided have a significant impact on the level of adoption.